Utilization of Third Generation Cephalosporins in Multispeciality Teaching Hospital, Dehradun - Bisht, Rekha; S, Bhattacharya; A, Katiyar (Indian Journal of Pharmacy Practice)
Antibiotic resistance has become a major clinical and public health problem within the life time of most people living today. The liberal use of third-generation cephalosporins in hospitals has been associated with the emergence of extended-spectrum beta- lactamases presenting concerns for bacterial resistance in therapeutics. The present study was carried out to identify the utilization of third generation cephalosporins in tertiary care teaching hospital in Dehradun. Total 250 inpatients were interviewed by using a data collection form. The study revealed that out of 250 patients, 213 were prescribed third generation cephalosporins. Ceftriaxone (46%) was most widely prescribed drug followed by cefixim (20.18%), ceftazidime (12.25), cefotaxime (8.92) and cefpodoxime (5.63).The maximum use of third generation cephalosporins was in medicine ward (39%) followed by patients in surgical (59, 28%), gynecology (36, 17%), orthopedic (18, 8%) and pediatric ward (9, 4%). The most common reasons for administration of third generation cephalosporins were high grade fever and gastrointestinal infections (26.29%) followed by respiratory tract infections (33,15.49%), injury cases (43, 20.19%), urinary tract infection (35,16.43%), skin and soft tissue infection (19,8.9%) and septicemia (04, 1.88%) and maximum patients were between the age group of 41-50 (23.47%) who were prescribed third generation cephalosporins
Keywords: Antibiotic; Resistance; Third generation cephalosporins; Prescription; infections